(untitled) (Comunicação & Inovação, 2016)
This article used the Cultural Analytics methodology (MANOVICH, 2011) to analyze the urban visual narrative of Praça da Alfândega, tourist site in the center of Porto Alegre, in two periods, during and after the Book Fair, comparing them and pointing indications of a visual language formation characteristic of that place. We conclude that the records made during the event reveal a social connection and a sense of belonging to the community, thereby transforming the place in space, where socialization reappropriates the meanings of the geography of interactions.